Enrichment of PHA-accumulators for sustainable PHA production from crude glycerol - Mohamad Fauzi, Ainil Hawa; Chua, Adeline Seak May; Yoon, Li Wan; Nittami, Tadashi; Yeoh, Hak Koon (Elsevier, 2019)
Polyhydroxyalkanoates (PHAs) as biodegradable polymers produced by microorganisms with thermo-plastic properties are of high interest. In this study, PHA-accumulators were cultivated using crude glycerol and activated sludge in a sequencing batch reactor (SBR) with the aerobic dynamic feeding (ADF) strategy. This study aimed to enrich PHA-accumulators by evaluating the stability of the cultivation reactor followed by the effect of organic loading rate (OLR). The cultivation reactor was stable while maintaining a steady feast/famine (F/F) ratio. The increase of OLR from 360 mgC/(L·d) to 1000 mgC/(L·d) led to the increment of biomass concentration from less than 0.7 g/L to 2 g/L. The enriched mixed culture produced a maximum PHA content of 80 wt% in biomass dry weight with a production yield of 0.7 mg C PHA/mg C. The mixed culture were found to accumulate both 3-hydroxybutyrate (3HB) and 3-hydroxyvalerate (3 HV) monomers at a HB:HV molar ratio of 60:40. Based on fluorescence in situ hybridization (FISH) analysis, Alphaproteobacteria and Betaproteobacteria were the most dominant species during peak PHA production. This method provides an option for resource recovery operation in converting waste to value-added products.